2018
DOI: 10.1242/dev.155929
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity within the niche ensures the maintenance of a Sox2+ stem cell population in the mouse incisor

Abstract: In mice, the incisors grow throughout the animal's life, and this continuous renewal is driven by dental epithelial and mesenchymal stem cells. is a principal marker of the epithelial stem cells that reside in the mouse incisor stem cell niche, called the labial cervical loop, but relatively little is known about the role of the stem cell population. In this study, we show that conditional deletion of in the embryonic incisor epithelium leads to growth defects and impairment of ameloblast lineage commitment. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 57 publications
(98 reference statements)
2
40
0
Order By: Relevance
“…The observed molecular heterogeneity may indicate the presence of several SC populations which each generate one or more tooth epithelial lineages; alternatively, the diverse molecular pattern may indicate a variety of stemness states of a single SC progeny. Our flow cytometry analysis demonstrated the diversity of Sox2-GFP+ SC population, in which some cells also express Ptch1, or, as recently reported, Lgr5 32 .…”
Section: Discussionsupporting
confidence: 87%
“…The observed molecular heterogeneity may indicate the presence of several SC populations which each generate one or more tooth epithelial lineages; alternatively, the diverse molecular pattern may indicate a variety of stemness states of a single SC progeny. Our flow cytometry analysis demonstrated the diversity of Sox2-GFP+ SC population, in which some cells also express Ptch1, or, as recently reported, Lgr5 32 .…”
Section: Discussionsupporting
confidence: 87%
“…While no homolog of Lgr5 exists in teleost fishes, lgr4 was expressed in cichlid RT and TBs more similarly to that of sox2 , although more restricted to the basal layers of epithelium in and around the taste unit. This is an intriguing result, given that Lgr5 + cells replenish Sox2 + cells after genetic deletion of Sox2 in mouse incisors (8). igfbp5 , shown coincident in expression to lgr5 in gecko RT dental lamina (38), indeed colabels the basal epithelial cells associated with the regenerating RT–TB unit.…”
Section: Resultsmentioning
confidence: 89%
“…Classic work demonstrated that Sox2 marks the putative ESC niche in a cadre of mammals and reptiles (4), bony fishes (5), and sharks (1, 6). Genetic fate mapping experiments show that Sox2 + ESCs contribute to all lineages of the dental epithelium (7, 8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the lineage tracing in this study clearly indicates that Sox2(+) cells contribute to the supernumerary tooth formation in GAG-deficient incisors, deleting Sox2 from Fam20B-deficient dental epithelium only partially rescued the phenotype. Sanz-Navarro et al [50] also observed mild tooth phenotypes when they removed Sox2 from Shh(+) population in the dental epithelium. They speculated that it may be related to the mosaic activation of Shh-Cre and/or redundancy from other Sox members.…”
Section: Discussionmentioning
confidence: 97%